Teacher knowledge in English language teaching: an analysis of its socio-historical construction in the western central region of Costa Rica / Saber docente en profesores de inglés: un análisis sobre su construcción socio-histórica en la región central... - Araya Araya, Karla; Córdoba González, Gustavo (Universidad de Costa Rica, 2008)
This article results from a research project developed in Costa Rica, specifically, in the central western region. Its main objective is of findings that shed light on the socio-historical principles and construction of teacher knowledge of English language teaching. Teacher knowledge is approached as a discursive and everyday life construction whose historical antecedents influence its constitution and perception. Therefore, an analysis of the historical situations that justified the English language teaching in Costa Rica is provided. Also, it is analyzed the way(s) national institutions like the “Ministerio de Educación Pública” as well as the English language teaching major from “Sede de Occidente, Universidad de Costa Rica” have historically assumed and set the principles of teacher knowledge. This study concludes that there have been four main domains regulating the English language teacher knowledge. They are the technical, the institutional, the content and the economic domains. Este artículo es el resultado de un proyecto de investigación realizado en la Región de Occidente de Costa Rica. El principal objetivo es presentar los principios socio-históricos que han constituido el saber docente en la enseñanza de la lengua inglesa. Desde el punto de vista teórico, se aborda (como propuesta) el saber docente como una construcción discursiva y cotidiana donde sus antecedentes históricos determinan su configuración e interpretación. Consecuentemente, se desarrolla un análisis discursivo de las condiciones históricas que justificaron la enseñanza del inglés en Costa Rica así como la forma en que el Ministerio de Educación Pública y la carrera del bachillerato en la enseñanza del inglés ?Universidad de Costa Rica, Sede de Occidente- han percibido y desarrollado el tema del saber docente. Finalmente, se concluye que, en Costa Rica, el saber docente en la enseñanza del inglés esta principalmente construida bajo cuatro aspectos aquí denominados como: dominio técnico, dominio institucional, dominio de contenido y el dominio económico.